THE INFLUENCE OF SERVICE QUALITY, PRODUCT QUALITY AND PRICE ON CUSTOMER SATISFACTION PT DIMENSI CITRA SEMESTA - Ridlolloh, Muhammad Fathin; Kusuma, Yanda Bara (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study aims to determine the effect of service quality, product quality, and price on customer satisfaction at PT Dimensi Citra Semesta. This type of research is quantitative research with a survey method. Data collection techniques were carried out by distributing questionnaires to 45 respondents. Data analysis techniques used multiple linear regression. The results showed that service quality, product quality, and price had a positive and significant effect simultaneously on customer satisfaction, partially Service Quality did not affect Customer Satisfaction at PT Dimensi Citra Semesta. Product Quality and Price variables had a positive and significant effect on Customer Satisfaction at PT Dimensi Citra Semesta.